Curative effects of gallic acid in honey bees (Apis mellifera) infected with Nosema ceranae - Kaya, Can Ayhan; Tatlı Seven, Pınar; Seven, İsmail; Aslan, Abdullah; Elbir, Nurgül; Çiftçi, Ayşe Türkan; İflazoğlu Mutlu, Seda (Springer France, 2026)
This study was aimed at evaluating the effects of gallic acid supplementation on spore load, survival, food consumption, and antioxidant status in honey bees (Apis mellifera) infected with Nosema ceranae. The bees used in the experiment were obtained from organic beekeeping operations with no disease history over the past two years. A total of 1200 newly emerged worker bees (0-3 days old) from disease-free colonies were randomly assigned to six experimental groups, each consisting of four subgroups of 50 bees. All groups were fed a 50% (w/v) sucrose solution. Ten bees from each group were sampled on days 3, 6, 9, 12, and 15. The experimental design included the following: Group 1 (Control), uninfected and fed only sucrose solution; Group 2 (N), infected with N. ceranae (1 & times; 10(6) spores/bee); Group 3 (G25), uninfected and fed gallic acid at 25 mg/kg; Group 4 (GN25), infected and fed 25 mg/kg gallic acid; Group 5 (GN50), infected and fed 50 mg/kg gallic acid; and Group 6 (GN100), infected and fed 100 mg/kg gallic acid. Gallic acid supplementation in infected bees significantly reduced spore load, an important indicator of infection severity (p < 0.001). The effect was dose- and time-dependent, with GN50 and GN100 showing greater efficacy, particularly by day 15 (p < 0.001). While gallic acid did not significantly alter bee survival or syrup consumption, it had notable effects on oxidative stress markers. Specifically, gallic acid significantly decreased MDA levels and enhanced GSH level and the activities of antioxidant enzymes GPx and CAT (p < 0.05) across all time points. These findings indicate that gallic acid may exert protective and reparative effects at the cellular level in Nosema ceranae-infected honey bees.
Keywords: Nosema ceranae; Gallic acid; Spore load; Food consumption; Antioxidant status; Honey bee